2009
DOI: 10.1537/ase.081114
|View full text |Cite
|
Sign up to set email alerts
|

Paralysis and severe disability requiring intensive care in Neolithic Asia

Abstract: This communication documents one of the earliest verifiable cases of human paralysis associated with severe spinal pathology. A series of skeletal abnormalities is described for a young adult male (M9) from a Southeast Asian Neolithic community. Differential diagnosis suggests that M9 suffered from a severely disabling congenital fusion of the spine (Klippel-Feil Syndrome, Type III), resulting in child-onset lower body paralysis at a minimum (maximally quadriplegia). M9 experienced severe, most probably total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 23 publications
0
30
0
2
Order By: Relevance
“…Paleopathology, broadly defined, includes both human and nonhuman cases, can be primarily medically oriented, and is focused on the manifestations or history of a disease itself and not necessarily on health-related inferences at the population level (Harper et al 2011;Marden and Ortner 2011;Telldahl 2012;Thomas and Johannsen 2011). More recently, the field has expanded in focus, with greater emphasis on disability identity, wellness, care and compassion, and sickness ideology (Hawkey 1998;Hubert 2000;Marsteller et al 2011;Oxenham et al 2009;Roberts 2000;Tilley and Cameron 2014;Tilley and Oxenham 2011). Osteobiography-focusing on individual prehistoric lives through bioarchaeological analysis-continues to exert a strong presence (Stodder and Palkovich 2012;Zvelebil and Weber 2013), reflecting the diversity of topics, including more humanistic ones, that paleopathologists explore.…”
Section: Introductionmentioning
confidence: 99%
“…Paleopathology, broadly defined, includes both human and nonhuman cases, can be primarily medically oriented, and is focused on the manifestations or history of a disease itself and not necessarily on health-related inferences at the population level (Harper et al 2011;Marden and Ortner 2011;Telldahl 2012;Thomas and Johannsen 2011). More recently, the field has expanded in focus, with greater emphasis on disability identity, wellness, care and compassion, and sickness ideology (Hawkey 1998;Hubert 2000;Marsteller et al 2011;Oxenham et al 2009;Roberts 2000;Tilley and Cameron 2014;Tilley and Oxenham 2011). Osteobiography-focusing on individual prehistoric lives through bioarchaeological analysis-continues to exert a strong presence (Stodder and Palkovich 2012;Zvelebil and Weber 2013), reflecting the diversity of topics, including more humanistic ones, that paleopathologists explore.…”
Section: Introductionmentioning
confidence: 99%
“…Only one archaeological case of Klippel–Feil documents the type of care the individual probably received directly due to their syndrome. In this instance, a young adult male discovered in Vietnam was probably quadriplegic due to his advanced Type III Klippel–Feil (Oxenham et al , ). Further evidence from his skeleton suggested that the individual was left incapacitated for the last decade of his life, completely relying on the welfare of others to feed and bathe him.…”
Section: Resultsmentioning
confidence: 99%
“…Documenting these social implications of treatment, good or bad, with pathological abnormalities or diseases should ultimately be included whenever possible with reconstructions of paleopathological conditions of prehistoric populations. Fay (: 192) points out that ‘palaeopathologists en masse have not addressed how disease as a conceptual structure was understood in the past, seemingly preferring a narrative grounded in present, biomedical paradigms.’ These types of considerations are just beginning to be discussed in the paleopathological literature, with the most notable interpretations of societal treatments based upon illness made by Marsteller et al () and Oxenham et al (). The social perspectives of a condition can change through time (Cross ).…”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that the finding of this type of congenital disorders in the bioarchaeological record can be the base for inferences about possible social behaviour, a complex issue to address from the archaeological record. One of the behaviours is related to the acceptance and inclusion of people who have developed these diseases within their communities, from a bioarchaeology of care perspective (Tilley & Cameron, ), even with the provision of some special and long‐term care, guaranteeing the lives of people with serious pathologies (Tilley & Oxenham, ), such as those described by Oxenham & coworkers () for a quadriplegic man who suffered severe Klippel–Feil syndrome. In the cases described in this work, malformations were not disabling for people suffering them; yet, it is possible that they may have limited or conditioned the performance of some daily activities.…”
Section: Discussionmentioning
confidence: 99%